A Methodology for Operationalizing Enterprise IT Architecture and Evaluating its Modifiability - Lagerström, Robert; MacCormack, Alan; Dreyfus, David; Baldwin, Carliss (Complex Systems Informatics and Modeling Quarterly, 2019)
Recent contributions to information systems theory suggest that the primary role of a firm’s information technology (IT) architecture is to facilitate, and therefore ensure the continued alignment of a firm’s IT investments with a constantly changing business environment. Despite the advances we lack robust methods with which to operationalize enterprise IT architecture, in a way that allows us to analyze performance, in terms of the ability to adapt and evolve over time. We develop a methodology for analyzing enterprise IT architecture based on “Design Structure Matrices” (DSMs), which capture the coupling between all components in the architecture. Our method addresses the limitations of prior work, in that it i) captures the architecture “in-use” as opposed to high level plans or conceptual models; ii) identifies discrete layers in the architecture associated with different technologies; iii) reveals the “flow of control” within the architecture; and iv) generates measures that can be used to analyze performance. We apply our methodology to a dataset from a large pharmaceutical firm. We show that measures of coupling derived from an IT architecture DSM predict IT modifiability – defined as the cost to change software applications. Specifically, applications that are tightly coupled cost significantly more to change.